1990
DOI: 10.1557/jmr.1990.0286
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic parallels between solid-state amorphization and melting

Abstract: A thermodynamics-based description, in the form of an extended phase diagram, of melting and solid-state amorphization is proposed which brings out the parallels between these two phenomena and suggests that their underlying causes are apparently the same. Through molecular dynamics simulations we demonstrate that every crystal, in principle, can undergo two different types of melting transitions with characteristic features that are also observed in radiation- and hydrogenation-induced amorphization experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(102 citation statements)
references
References 37 publications
6
96
0
Order By: Relevance
“…[4] It can be seen in Fig. 13 that the critical strains observed in the present work delineate the extension of the mechanical stability curve to temperatures below Tt.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…[4] It can be seen in Fig. 13 that the critical strains observed in the present work delineate the extension of the mechanical stability curve to temperatures below Tt.…”
supporting
confidence: 57%
“…It has been coz.jectured that in crossing this stability curve the lattice will become disordered, thus providing a simple thermodynamic connection between melting and solid-state amorphization. [4] What we have found is that in crossing such a curve the lattice does become mechanically unstable as manifested by sudden jumps in the hydrostatic pressure and the potential energy; however, the atomic configuration into which it evolves depends on the temperature. …”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The fi_ st of these results was somewhat surprising, since earlier computer simulat__ons c f the melting process in Cu [30] showed that the volume dependence of the shear mo_luli C44 and C' during homogeneous expansion at constant temperature was virtually identical to that associated with thermal expansion at constant pre., sure, which implies that the volume dependence of the elastic constant doe_ not depend on how the expansion is produced. However, it is now .…”
Section: Relationship Between Shear Modulus and Volume Expansionmentioning
confidence: 91%
“…[19][20][21][22] The melting criteria are often involved (e.g., the Lindemann criterion for the critical thermal displacement of atoms 2o , 22 and the Egami-Waseda criterion for the critical elastic strain caused by the atomic-size mismatch 23 ).…”
Section: Atomistic Modelsmentioning
confidence: 99%